2017
DOI: 10.1530/rep-17-0342
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between endometrial stromal cells and macrophages impairs cytotoxicity of NK cells in endometriosis by secreting IL-10 and TGF-β

Abstract: The dysfunction of NK cells in women with endometriosis (EMS) contributes to the immune escape of menstrual endometrial fragments refluxed into the peritoneal cavity. The reciprocal communications between endometrial stromal cells (ESCs) and lymphocytes facilitate the development of EMS. However, the mechanism of these communications on cytotoxicity of natural killer (NK) cells in endometriotic milieus is still largely unknown. To imitate the local immune microenvironment, the co-culture systems of ESCs from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 39 publications
(48 reference statements)
1
59
0
1
Order By: Relevance
“…However, there is increasing evidence for immunoregulatory NK cells that might mediate immune responses by secretion of interleukin (IL)-10, IL-4 and transforming growth factor (TGF)-b and/or might be responsive to these particular cytokines [2][3][4][5]. In a co-culture system, the interaction between macrophages and endometrial stromal cells was shown to down-regulate cytotoxicity of NK cells, possibly by stimulating the secretion of IL-10 and TGF-b [6]. In a co-culture system, the interaction between macrophages and endometrial stromal cells was shown to down-regulate cytotoxicity of NK cells, possibly by stimulating the secretion of IL-10 and TGF-b [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is increasing evidence for immunoregulatory NK cells that might mediate immune responses by secretion of interleukin (IL)-10, IL-4 and transforming growth factor (TGF)-b and/or might be responsive to these particular cytokines [2][3][4][5]. In a co-culture system, the interaction between macrophages and endometrial stromal cells was shown to down-regulate cytotoxicity of NK cells, possibly by stimulating the secretion of IL-10 and TGF-b [6]. In a co-culture system, the interaction between macrophages and endometrial stromal cells was shown to down-regulate cytotoxicity of NK cells, possibly by stimulating the secretion of IL-10 and TGF-b [6].…”
Section: Introductionmentioning
confidence: 99%
“…A robust reconstitution of immunoregulatory NK cells by day 14 after allogeneic stem cell transplantation is an important determinant of clinical outcome, and it has been suggested that NK cells may suppress the development of the T cell-mediated alloreactive immune response through production of IL-10 [4]. In a co-culture system, the interaction between macrophages and endometrial stromal cells was shown to down-regulate cytotoxicity of NK cells, possibly by stimulating the secretion of IL-10 and TGF-b [6]. Recent evidence provides support for the notion that natural killer T (NK T) cells (a small but important immunoregulatory T cell subset of human peripheral blood lymphocytes) play a pivotal role in pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β plays a key role in decreasing immune cells activity and promoting the implantation, growth and angiogenesis of endometrial tissue in the peritoneal cavity (Hull et al 2012). Although a high level of TGF-β is reported in the serum, PF and ectopic endometrium of women with EMS (Oosterlynck et al 1994, Pizzo et al 2002, Young et al 2014, our recent study confirmed that TGF-β could impair the cytotoxicity of NK cells (Yang et al 2017). In addition, it was reported that IDO expression is negatively correlated with the suppressor of cytokine signaling 3 (SOCS3) and positively correlated with TGF-β (Liu et al 2017).…”
Section: The Stimulatory Effect Of Ectopic Escs On Ido In Nk Cells Ismentioning
confidence: 50%
“…However, there are no treatments thus far due to the controversial pathogenesis of the disease. Despite anatomical, genetic, endocrine, environmental and dietary factors (Simpson et al 1980, Missmer et al 2004, Bulun 2009, Vannuccini et al 2016, accumulating evidence have showed that an aberrant immune microenvironment in the abdominal cavity plays a significant role in the initiation and progression of EMS by preventing retrograde menstruation from immune clearance, as well as allowing the attachment, implantation and angiogenesis of endometrial cells (Matarese et al 2003, Jeung et al 2016, Yu et al 2016, Yang et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation